The Public Perception of the Pensions System (Central Bank of Malta, 2010)
The New Pensions Working Group (NPWG) commissioned the National Statistics Office (NSO) to carry out a survey directed to obtain an understanding of the public's perception of the pensions system. The target population for this survey consisted of Maltese residents living in private households aged 18 to 63. An effective stratified sample of around 970 individuals was selected by NSO, such that each individual had an equal and independent chance of being selected. The stratification was performed by individuals' age, sex and district. (...)
Keywords: 330